Sosialisasi dan Pendampingan Literasi Keuangan dan Media Promosi Digital untuk UMKM Desa Bagon, Kecamatan Puger, Jember - Nurshadrina Kartika Sari; Yuniorita Indah Handayani; Muhammad Abdul Wafi; Mareta Susana; Dita Rahayu Artaningtias; Feby Astiwi Putri; Novem Bagus Pramesta (Jurnal Pengabdian Literasi Digital Indonesia, 2022)
Bagon Village, Puger District, Jember Regency has 15 MSMEs managed by the community as a livelihood, various types of businesses can be found in this village ranging from culinary, handicrafts and also service providers. The service partners in this activity are seven MSMEs in Bagon Village. The problems faced by partners are aspects of business management, which are related to business financial management and marketing aspects. To solve this problem, the team carried out socialization about financial literacy and digital promotional media, besides that the team also provided assistance to partners to practice using a business transaction recording application, namely Kasir Pintar and creating social media such as Instagram and Facebook, creating accounts on marketplaces such as Shopee. and register your business on Google My Business. The results obtained are increased knowledge and insight of partners in accessing financial applications and digital promotional media and optimizing these applications in the implementation of their daily business activities. The team also provides assistance so partners can compose interesting digital promotional content, such as creating promotional flyers. In the future, it is hoped that further assistance can be carried out based on the results of the evaluation by the team, so that partners can optimally use financial applications and promotional media.